2011
DOI: 10.1007/s00038-011-0265-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in smoking behavior among college students following implementation of a strict campus smoking policy in Taiwan

Abstract: Implementation of a strict smoking policy in college prompted smokers to markedly reduce smoking in campus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…This finding is supported by a study among US American college students showing that more heavy smokers are less likely to quit (Berg et al, 2012). Since quitting smoking was also positively associated with agreement with university campus smoking ban, smoke-free environments are likely to support quit attempts as research from a Taiwanese campus suggests (Chuang and Huang, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by a study among US American college students showing that more heavy smokers are less likely to quit (Berg et al, 2012). Since quitting smoking was also positively associated with agreement with university campus smoking ban, smoke-free environments are likely to support quit attempts as research from a Taiwanese campus suggests (Chuang and Huang, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…smoking should ban in public places; penalty should be given to smokers in public places) compared to non smokers which is also supported by our findings. Despite that more than 50% of college students reported beginning or substantially increasing smoking behaviour in college , nevertheless an encouraging point is that in Taiwan, the implementation of a strict campus smoking policy showed that smokers modified their smoking behaviour and attitude: they felt that smoking was unwelcome, and thus reduced smoking in campus and thought about quitting (Chuang and Huang, 2011).…”
Section: Factors Associated With Smoking Quit Attempts and Attitudmentioning
confidence: 99%
“…Indeed gender has been proposed as a predictor of smoking (Al-Naggar et al, 2011), and quitting (Osler et al 1999). Nevertheless, in Taiwan, there were changes in smoking behaviour among college students following implementation of a strict campus smoking policy, where the reasons cited by the smoker students for the behaviour change comprised four themes: a changed smoking experience, change in social norm, the respect for law, and concern for others' health (Chuang and Huang, 2011). Likewise, in the USA, enforcing an outdoor smoking ban using a multiple component package increased compliance with the non-smoking policy on college campus (Harris et al, 2009).…”
Section: Factors Associated With Smoking Quit Attempts and Attitudmentioning
confidence: 99%
See 2 more Smart Citations